CuS nanoparticles: An efficient electrocatalyst for hydrogen evolution reaction in a wide pH range. (10th February 2023) - Patel, Meswa; Joshi, Kinjal K.; Modi, Krishna H.; Pataniya, Pratik M.; Siraj, Sohel; Sahatiya, Parikshit; Sumesh, C.K.
Abstract: The design and fabrication of eco-friendly, highly sustainable and efficient, and non-noble metal-based electrodes are in high demand for the hydrogen evolution reaction (HER) in a wide pH range. Herein, we report the synthesis CuS nanoparticles and fabrication of paper-based electrodes. Robust and electrocatalytically active CuS nanoparticles shows the obvious hydrogen evolution reaction in broad pH range. Flexible, large area and binder free electrodes on paper substrate show the efficient catalytic performance in HER with small over potentials of 79, 258, 375 mV at 10 mA/cm 2 in 0.5 M H2 SO4, 0.5 M KOH, and 3 M NaCl, respectively. This result shows the highly active and stable electrocatalyst for HER in a wide pH range. Encouragingly, CuS/Ag/Paper electrodes advocates the significant technical development for industrial level hydrogen gas.